Corrected QT Interval Prolongation Complicating Incoercible Vomiting in a Coronavirus Disease 2019 Patient Under Chloroquine and Azithromycin - Nassih, Houda; Fakiri, Karima El; Qadiry, Rabiy El; Bourrahouat, Aicha; Sab, Imane Ait (Cardiology and Cardiovascular Medicine, 2020)
Administration of chloroquine with azithromycin for the treatment of coronavirus disease 2019 (COVID-19) carries increased risk of corrected QT interval (QTc) prolongation and cardiac arrhythmias. But it is difficult to identify the real cause of QTc prolongation when two or more risk factors are gathered. This was the case of our female patient presenting with QTc prolongation after starting chloroquine and azithromycin.